In vitro screening of multidrug resistance uropathogenic Escherichia coli from the urban area of Namakkal district - Arjunan Gnanasekaran, Perumal Manikandan, Palani Poongothai, Palani Kandasamy Senthilkumar, Jagadeeshkumar Vigneshwari (Journal of Applied Pharmaceutical Science, 2019)
The aim of the study is to screen the multiple drug resistance (MDR) Uropathogenic Escherichia coli (UPEC) from the urban area of Namakkal district. To detect UPEC resistant by using different antibiotics and to analyze the virulent characteristics of UPEC and amplification of extended-spectrum beta-lactamases genes by multiplex polymerase chain reaction. Total 450 samples individually collected from the urinary tract infection (UTI) patients’ and direct streaked on to the eosin methylene blue agar plates. Significant growth indicates E. coli. HiCrome UTI agar was used for rapid identification of uropathogenic E. coli. Out of 450 samples, only 62 isolates of E. coli were subjected to virulence characteristics, such as slime production (34%), hemolytic activity (56%), and beta-lactamase production (43%). Antibiotic sensitivity test was performed with 13 different antibiotics. Among them, 62 isolates were E. coli, only five were resistant to 10 antibiotics, possess virulence characteristics. Four strains (E-12, E23, E-58, and E-97) have Temoneira, sulfhydryl variable, and cefotaxime hydrolyzing capabilities (CTX-M) antibiotic resistance genes, and E-07 have only CTX-M gene. As E. coli is the main infectious agent in patients with UTI and a potent pathogen, it was difficult to treat with routine antibiotics because day-by-day microbes are resisting to common drugs. Hence, they need alternative therapy.
Keywords: Multidrug resistance, uropathogenic Escherichia coli, HiCrome UTI agar, extended-spectrum beta-lactamase, hemolytic, slime, multiplex PCR.